2016
DOI: 10.1200/jop.2015.008904
|View full text |Cite
|
Sign up to set email alerts
|

Use of Survivorship Care Plans and Analysis of Patient-Reported Outcomes in Multinational Patients With Lung Cancer

Abstract: For patients with lung cancer worldwide, it is feasible to obtain PROs and to create SCPs through an Internet-based program. As patients with lung cancer achieve improved survival, further attention should be paid to PROs. Surprisingly, neurocognitive symptoms seem to be the most common issues and therefore the most important to address. Increased effort should be made to provide SCPs, particularly in urban and university cancer center settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
(18 reference statements)
0
19
0
Order By: Relevance
“…Furthermore, this number is lower than previous studies utilizing responses from the OncoLink SCP tool for other cancer sites (16)(17)(18)(19). As many pancreatic cancer patients are anticipated to live with incurable disease from time of diagnosis or to relapse soon after treatment, providers may defer provision of an SCP.…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, this number is lower than previous studies utilizing responses from the OncoLink SCP tool for other cancer sites (16)(17)(18)(19). As many pancreatic cancer patients are anticipated to live with incurable disease from time of diagnosis or to relapse soon after treatment, providers may defer provision of an SCP.…”
Section: Discussionmentioning
confidence: 63%
“…For example, utilizing OncoLink PRO of lung cancer patients, it was determined that neurocognitive and musculoskeletal side effects caused a high incidence of morbidity, something that physicians did not focus on for this particular disease site. 31 In the study reported here, survivors reported some toxicities, such as dysphagia, that might have been anticipated by providers, but reported others, such as fatigue, that are often minimized by health care providers despite significant impact on quality of life.…”
Section: Discussionmentioning
confidence: 66%
“…That so few survivors report previous receipt of survivorship information suggests that these communication tools are still underutilized in this population. Furthermore, this number is lower than previous studies utilizing responses from the OncoLink SCP tool for other cancer sites (16)(17)(18)(19). As many pancreatic cancer patients are anticipated to live with incurable disease from time of diagnosis or to relapse soon after treatment, providers may defer provision of an SCP.…”
Section: Discussionmentioning
confidence: 90%